2016
DOI: 10.1111/jir.12298
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of reported physical health problems in people with severe or profound intellectual and motor disabilities: a cross‐sectional study of medical records and care plans

Abstract: The results suggest that people with SPIMD simultaneously experience numerous, serious physical health problems. The reliance on reported problems may cause an underestimation of the prevalence of health problems with less visible signs and symptoms such as osteoporosis and thyroid dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
78
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 37 publications
1
78
5
2
Order By: Relevance
“…challenging behavior), and health problems [4][5][6]. Research by Van Timmeren, Van der Putten, Van Schrojenstein Lantman-de Valk, Van der Schans, and Waninge [6] has shown that an individual with VSPID has on average 12 health problems; in more than 50% epilepsy, spasticity, constipation, incontinence, deformations, and reflux has been reported. These problems of adults with VSPID are interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…challenging behavior), and health problems [4][5][6]. Research by Van Timmeren, Van der Putten, Van Schrojenstein Lantman-de Valk, Van der Schans, and Waninge [6] has shown that an individual with VSPID has on average 12 health problems; in more than 50% epilepsy, spasticity, constipation, incontinence, deformations, and reflux has been reported. These problems of adults with VSPID are interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…Constipation was more common in those with cerebral palsy and profound intellectual disability, and associated with immobility but not age, suggesting that constipation is a significant issue for people with intellectual disability across the life course. In a further recent study, of 99 people with severe or profound intellectual and motor disabilities, 94% had constipation (van Timmeren, van der Putten, Lantman‐de Valk, van der Schans, & Waninge, ).…”
Section: Introductionmentioning
confidence: 95%
“…People with intellectual disability tend to experience more health problems, but poorer access to medical health services (Alborz, McNally, & Glendinning, 2005; Backer, Chapman, & Mitchell, 2009; Krahn et al, 2006; Williamson et al, 2017). As a consequence, they are more likely than others to live their lives with unrecognised and unmet health needs (van Timmeren, van der Putten, van Schrojenstein Lantman‐de Valk, van der Schans, & Waninge, 2016). Regular health screening in primary care is seen as an efficient means to identify unmet health needs (Baxter et al, 2006; Robertson, Hatton, Emerson, & Baines, 2014).…”
Section: Introductionmentioning
confidence: 99%